Operational Management Practices for Employee Job Satisfaction and Employee Retention: A Study at SJ Security - Samuel Ray Setiawan (Journal Research of Social Science, Economics, and Management, 2026)
Employee retention has become a critical organizational challenge in labor-intensive service industries, particularly in security outsourcing companies, where workforce stability directly affects service continuity and operational effectiveness. SJ Security, a multi-site security outsourcing company, experienced recurring operational issues characterized by inconsistent communication, uneven task allocation, and variations in operational practices across supervisors and work sites, indicating that consistency in operational management remained a key organizational concern. This study aimed to identify operational management issues and examine how these practices influenced employee job satisfaction and retention at SJ Security. A qualitative approach was employed using semi-structured interviews with nine participants, consisting of six security personnel, two operational supervisors, and one management representative. The interviews explored employees' experiences related to communication, task allocation, operational consistency, and supervisory support. The data were analyzed using thematic analysis, root cause analysis, Pareto analysis, and priority ranking. The findings identified four major themes: communication and operational coordination, fairness in task allocation, operational consistency, and performance monitoring and employee support. Communication inconsistency and unfair task allocation emerged as the primary areas requiring improvement because they were consistently associated with employees' perceptions of organizational support and workplace fairness. Employee retention was found to develop gradually through repeated workplace experiences, with recurring communication gaps, inconsistent operational practices, and perceived unfairness progressively reducing employees' intentions to remain with the organization. Based on these findings, three improvement strategies were proposed: communication standardization, equitable task allocation, and operational management standardization, to be implemented in phases.